(untitled) (Global Journal of Human-Social Science, 2017)
Identification of groundwater aquifer in hard rock using conventional surface geophysical investigation techniques is intricate in nature. Numerous attempts have been made in the recent past to understand and identify appropriate technique(s) to locate deeper fracture zones (pay zones), its dimension and orientation, transient variations due to moisture etc., which are the prime cause of complexity in identifying groundwater. Simply a practical approach to locate groundwater aquifer could be to carry out surfacial geophysical investigation(s) in unison with tracer studies and also to look out for favorable geological settings in an area. One such approach initiated in granite terrain of southern India is described in this paper. In this manuscript the author illustrates surface geophysical and tracer techniques adopted in deciphering a buried dolerite dyke occupying a fault, also happen to bifurcate/truncate shallow aquifer into two independent segments during pre-monsoon which otherwise appears as a single unit after monsoon. This integrated study has proven to be exceptionally useful in this hydrological investigation and may be extended for similar complicated situations.